The Inquiry Learning Model Uses Small Steps Technique Google Drive on Chemistry Learning Student Class X TAV at SMK PIRI 1 Yogyakarta - Hadiyanto Sahputra (International Journal of Chemistry Education Research, 2018)
ABSTRACT: The aim of this study is to know the learning method of Inquiry Learning Small Steps in the chemistry subject through online learning with Google drive media. This study includes an assessment of learning activities and student achievement in chemistry lesson. Object of this study were students of X Class of Technical Audi-Video program (X TAV) in the academic year 2016/2017 of SMK PIRI 1 Yogyakarta. The number of objects examined were 15 students consisting of 15 male and 1 female students. Stages of inquiry learning is providing problems, formulating problems, making hypotheses, collecting data, examining hypotheses and making conclusions. Data collection using observation sheets, tests and questionnaires. The data obtained were analyzed descriptively. Based on the research results obtained that: (1) The use of google media drive can increase student learning activity in the material of atom structure in chemistry lesson. This can be seen from the value of student activity with score 4 (good), student's response value is 85% (Very Positive) and the value of student learning result Pre cycle is 41%, Cycle 1: 54% and Cycle 2: 85%Keywords: Learning inquiry, google drive media, media learnerReceived: 16 January 2018, Revised: 22 January 2018, Accepted: 24 February 2018